Development of cellulose acetate/CuO/AgNP nanofibers based effective antimicrobial wound dressing. (April 2023) - Kumar, Gul; Khan, Faraz Gaji; Abro, Muhammad Ishaque; Aftab, Umair; Jatoi, Abdul Wahab
Abstract: The research reports synthesis of the CuO/AgNP composite nanoparticles and their electrospun cellulose acetate (CA) nanofiber for effective and safer antimicrobial wound dressing applications. Synthesis of the composite nanoparticles was confirmed by XRD, TEM and EDS analysis. The SEM confirmed regular morphologies of the composite nanofibers. CA nanofibers with three different concentrations of CuO/AgNPs (3%, 6% and 10%) were fabricated. The Kirby-Buyer disk diffusion test and relative cell viability results confirmed sufficiently larger bacteriostatic and bactericidal properties of the nanocomposites. The water absorption/transport, swelling ratio and tensile strength results revealed the nanocomposite's potential for the application. Our findings suggested the CA/CuO/AgNP as effective antimicrobial wound dressing material. Graphical abstract: Image 1 Highlights: CA/CuO/AgNP nanocomposites were prepared for antimicrobial wound dressings. The wound dressings were designed for effective and safer antimicrobial activities. The AgNPs anchored on CuO nanoparticles produced effective microbial protection. The results confirmed effectiveness of the designed construct for antimicrobial wound dressings.